A diagnostic approach to popliteal fossa masses. Issue 4 (April 2017) - Shah, A.; James, S.L.; Davies, A.M.; Botchu, R.
Abstract : There is a myriad of potential mass lesions that occur in the popliteal fossa, which present as palpable masses or are found incidentally on imaging. With a thorough knowledge and understanding of the appearances and locations of these different entities, one can narrow the differential diagnoses in the majority of cases. This will eliminate unnecessary additional investigations and enable a more rapid management. We present a review of frequently encountered and less common entities using an anatomical sieve, with the aim of providing a diagnostic approach to popliteal fossa masses.